Trauma-informed psychological supports when natural disasters come - Williams, York (Victimology, 2022)
Natural calamities like earthquakes, landslides, volcanoes, hurricanes, tornados, and cyclones, flooding, extreme temperature, wildfires destroy life and environment. The victims of natural calamities face economic and social crisis in addition to the loss of dear ones. This chapter will focus on the psychological reactions through a trauma lens of the victims when faces natural calamities and psychological aids to be provided. The chapter will also deal with the stages and reactions of counsellors or volunteers at natural calamity sites, and psychological precautions and interventions to be taken care to prevent the vicarious trauma, compassion fatigue, and burnout. It will also describe the individual and group therapies and rehabilitation at individual and community levels.